ELSA Speak as Mobile Assisted Language Learning To Improve Students’ Speaking Skill - Annisa Nabila Rizqa Putri; Abdul Muin; Tri Ilma Septiana (LPPM Universitas Bina Sarana Informatika, 2024)
This study endeavors to explore whether there exists a significant discrepancy in students' speaking proficiency between those instructed with the ELSA Speak application and those without it, among twelfth-grade students at SMAN 6 Kota Serang. Employing a quantitative research approach with a quasi-experimental method, the researcher examined 60 twelfth-grade students from SMAN 6 Kota Serang, comprising 30 students from XII MIPA-6 as the experimental group and another 30 students from XII MIPA-3 as the control group. Data collection methods encompassed observation, pre-tests, treatment, and post-tests. Analysis via t-test yielded revealing results: the mean speaking proficiency score for the experimental group was 76.93, while for the control group it stood at 64.26. Furthermore, the calculated t-value was 8.46, surpassing the critical t-value of 1.67 at a significance level of 5%. This disparity between the obtained t-value and the critical t-value led to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (Ho). In essence, the findings suggest a significant disparity in speaking proficiency between the group using the ELSA Speak application and the group without it. Consequently, these results underscore the importance of integrating technology-based language learning tools such as ELSA Speak into educational curricula, as they have demonstrated efficacy in enhancing students' speaking skills and fostering more effective language acquisition. Key words: ELSA Speak, Speaking Skill, Mobile Assisted Language Learning.